2017
DOI: 10.1016/j.colsurfb.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of Cu on Ti-Nb-Ta-Zr sputtered uniform/adhesive gum films accelerating bacterial inactivation under indoor visible light

Abstract: a b s t r a c tThis article presents the evidence for the significant effect of copper accelerating the bacterial inactivation on Ti-Nb-Ta-Zr (TNTZ) sputtered films on glass up to a Cu content of 8.3 at.%. These films were deposited by dc magnetron co-sputtering of an alloy target Ti-23Nb-0.7Ta-2Zr (at.%) and a Cu target. The fastest bacterial inactivation of E. coli on this later TNTZ-Cu surface proceeded within ∼75 min. The films deposited by magnetron sputtering are chemically homogenous. The film roughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Their results are consistent with the long-range mobility of conduction band electrons being strongly influenced by grain boundaries. Consequently, optimizing the crystals/particles size while keeping high enough surface area will be an significant way onward [66][67][68][69].…”
Section: Cu Coupled With Tio 2 Sputtered Surfaces Active In the Visibmentioning
confidence: 99%
“…Their results are consistent with the long-range mobility of conduction band electrons being strongly influenced by grain boundaries. Consequently, optimizing the crystals/particles size while keeping high enough surface area will be an significant way onward [66][67][68][69].…”
Section: Cu Coupled With Tio 2 Sputtered Surfaces Active In the Visibmentioning
confidence: 99%
“…Highly pathogenic biofilms can strongly adhere to textiles, glass surfaces, prostheses, catheters, dental implants, and metal plates. Ag film morphology and grain size have been addressed in Ag films leading to bacterial inactivation . More advanced and effective antibacterial surfaces are a subject of timely interest, and in this direction silver and copper nanoparticles have recently been addressed in studies reporting antibacterial surfaces/films, carbon nanotubes, , diamond-like carbon, , metal oxides, nitrides, and oxynitrides. …”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies [13][14][15], we reported the mechanical properties of a superelastic Ti-based GMTF showing increased bacterial inactivation under light concomitant to a biocompatible property in darkness [16,17]. We also showed the effect of copper content on the structure, morphology, and mechanical properties of GMTF [18]. We also showed that the TNTZ-Cu 8.3 at % Cu sample with the highest roughness (RMS value of 20.1 nm) led to the highest bactericidal activity.…”
Section: Introductionmentioning
confidence: 71%